Laws of documentary-communication sciences: correlation with science of science knowledge (part 3) - E. I. Poltavskaya (Библиосфера)
In accordance with philosophical concepts of a scientific law the third article discusses the laws of bibliopsychology, laws of the information space development and theoretical ones of documentative communicology, which unites allied documentary-communication sciences (library science, bibliography science, bibliology, archival science, museology).